Markers of Oxidative Stress in Dogs with Myxomatous Mitral Valve Disease are Influenced by Sex, Neuter Status, and Serum Cholesterol Concentration. (29th January 2017) - Reimann, M.J.; Häggström, J.; Møller, J.E.; Lykkesfeldt, J.; Falk, T.; Olsen, L.H.
Abstract : Background: Cardiovascular disease has been associated with oxidative stress, which has been suggested to contribute to myocardial remodeling in human patients. Little is known about the relationship between myxomatous mitral valve disease (MMVD) and oxidative stress in dogs. Objective: To determine whether clinical stage of MMVD is associated with changes in the plasma concentrations of certain markers of oxidative stress in clinically healthy dogs and dogs with MMVD. Animals: Seventy five privately owned dogs: 59 cavalier King Charles Spaniels (CKCS) with different severities of MMVD and 16 dogs of different breeds with clinical signs of congestive heart failure (CHF) caused by MMVD. Methods: Markers of oxidative stress including malondialdehyde (MDA), oxidized low‐density lipoprotein (oxLDL), and vitamin E (α‐tocopherol and γ‐tocopherol) were measured in plasma and their association with clinical stage of MMVD was assessed by regression analyses. Results: Plasma oxLDL concentration was significantly lower in female dogs compared with males ( P = .01). Significantly higher plasma γ‐tocopherol concentrations were found in neutered ( P = .003) dogs. Vitamin E (α‐tocopherol [ P = .0004] and γ‐tocopherol [ P = .003]) was associated with body condition score (BCS), but the association disappeared when cholesterol was included in the analyses. All markers of oxidative stress (MDA, oxLDL, and vitamin E) were positively associated with serum cholesterol concentration ( P ≤ .04), but none were associated with clinical stage of MMVD. Conclusions: In conclusion, markers of oxidative stress are associated with sex, BCS, neuter status, and cholesterol. The results cannot confirm a relationship between oxidative stress and clinical stage of the disease in dogs with MMVD.